The law book - Chrisp, Peter (Big ideas simply explained., 2020)
Presents the history of law and how it has evolved over the years, and examines how laws, legal precedents, and religious, moral and political codes have shaped the world we live in. Provides historical context for important laws, and includes photographs and illustrations, fact boxes, maps, timelines, a directory, and a glossary.